2019
DOI: 10.2166/aqua.2019.049
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of water shortage crisis in the Middle East and possible remedies

Abstract: Water resources in the Middle East region are becoming scarce, while millions of people already do not have access to adequate water for drinking and sanitary purposes. Water resources depletion has become a significant problem in this region that is likely to worsen. Current research by remote sensing analysis indicates a descending trend of water storage in the Middle East region, where agriculture plays a crucial role in socio-economic life. This study introduces an approach quantifying water depletion in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…Bozorg-Haddad et al [43] studied the water scarcity in the Middle East region (including Iraq) by Gravity Recovery and Climate Experiment remote-sensing technique, their analysis indicates descending trend of water storage in the region. The two water scarcity indices, water equivalent anomaly (WEA) and total water storage (TWS) depletion calculated and revealed that the region has very negative water scarcity indices.…”
Section: Wft (Mmentioning
confidence: 99%
“…Bozorg-Haddad et al [43] studied the water scarcity in the Middle East region (including Iraq) by Gravity Recovery and Climate Experiment remote-sensing technique, their analysis indicates descending trend of water storage in the region. The two water scarcity indices, water equivalent anomaly (WEA) and total water storage (TWS) depletion calculated and revealed that the region has very negative water scarcity indices.…”
Section: Wft (Mmentioning
confidence: 99%
“…The Middle East is located in the southwest of Asia and is well known for its significant energy resources such as oil and gas. Due to the semiarid and arid climates in large parts of the Middle East, this region always faces a water shortage crisis [1]. During the last few decades, due to the intense growth of the population and industries, the importance of water resources has considerably increased in this region [2].…”
Section: Introductionmentioning
confidence: 99%
“…There are two main clustering methods: hierarchical and non-hierarchical cluster analysis. Hierarchical clustering (used in this study) combines cases into homogeneous clusters where objects at one level are combined with objects at another level and produce clusters that are not allowed to overlap (Bunkers and Miller, 1996;Yim and Ramdeen, 2015). Two different strategies for hierarchical clustering exist: agglomerative and divisive (Lior and Maimon, 2005).…”
Section: Cluster Analysismentioning
confidence: 99%
“…Scientists have also warned that the water shortage will continue further in the coming decades in the Middle East, where water is one of the most valuable and vulnerable natural resources (Mehryar et al, 2015;Ashraf et al, 2019;Bozorg-Haddad et al, 2020). Iran is one of the countries suffering a freshwater shortage and climate change consequences (Karimi et al, 2018;Afshar and Fahimi, 2019;Emami and Koch, 2019;Naderi, 2020).…”
Section: Introductionmentioning
confidence: 99%